Learning Atmosphere and Ethical Behavior, Does It Make Sense? - Camps, Joaquín (Journal of business ethics, 2010)
In the wake of corporate ethical scandals that have harmed millions of employees and investors, there has been an increase in the number of works written in the last decade, which aim to answer one apparently simple question: what causes unethical behavior, and what can we do, if anything, to prevent similar transgressions in the future? The extensive research around this question is the best proof of its real complexity as the challenge of disentangling the background of ethical behavior has obvious academic and practical interest. This study aims to take a further step toward that goal. Much research has noted the impact of multiple aspects of organizational contexts on individuals’ ethical behavior. However, studies that analyze the impact of organizational learning capability (OLC) on employees’ ethical behavior are few and far between. This was the first aim of this study. The second centered on gaining a deeper understanding of the relationship between OLC and ethical behavior by analyzing the mediating role of employability and organizational commitment. We tested our hypotheses through a structural equation methodology applied to a sample of 641 workers from 166 Spanish consultancy firms and found a positive, direct relationship between OLC and employability, OLC and organizational commitment, employability and organizational commitment, and organizational commitment and ethical behavior.